PENYULUHAN MENINGKATKAN RESILIENSI REMAJA TERHADAP SEKS BEBAS, HIV/AIDS DAN NARKOBA PADA SISWA SMA DI KECAMATAN SUKAWATI TAHUN 2019 - Gusti Ayu Marhaeni (Poltekkes Kemenkes Denpasar, 2020)
Adolescence is a turbulent period in which mood changes very quickly. Teenagers tend to rebel, and measure everything with their own size, so teens often do things that are outside the norm to get recognition. Besides that the influence of peers is very dominant in adolescent behavior, so it often happens adolescents are involved in negative things, including engaging in drugs, free sex and may fall into the condition of HIV / AIDS.The aim of community service is an increase in adolescent resilience to free sex, drugs and HIV / AIDS. The method of community service carried out in the form of lectures, questions and answers and equipped with leaflet media. The activity was carried out on 19 and 26 June 2019 to collect pretest and posttest data. The activity targets amounted to 68 students consisting of 26 male students and 42 female students. The results of community service activities show there are differences in resilience before and after treatment for both male and female students. Suggestions are given so that the school routinely holds similar activities so that students are always exposed to health information that will be beneficial for healthy behavior. Keywords: Teenage Resilience, Free Sex, HIV / AIDS and Drugs